A low-noise and flexible FPGA-based binary signal measurement generator. Issue 5 (18th March 2019) - Notzon, Gordon; Storch, Robert; Musch, Thomas; Vogt, Michael
Abstract: In the area of electromagnetic metrology, binary coded excitation signals become more and more important and various binary coded sequences are available. The measurement approach is to assess the impulse response function of a device under test by correlating the response signal with the excitation signal. In order to achieve a high measurement reproducibility as well as a high dynamic range, the generated binary coded signals have to provide low-noise. In this contribution, a low-noise signal generator realized with a field programmable gate array is presented. The performance investigation of different kinds of binary coded excitation signals and different correlation concepts have been practically investigated. With a chip rate of 5 Gchip/s, the generator can be utilized for ultra-wideband applications. In order to allow for a low-noise and long-term stable signal generation, a new clock generator concept is presented and results of phase noise measurements are shown. Furthermore, an algorithm to fast and precisely shifting the time lag between two binary coded signals for correlating excitation and response signals with a hardware correlator is presented. Finally, the realized demonstrator system is tested using two commonly used types of binary coded sequences.